The Effect Of Emotional Intelligence And Organizational Commitment On Employee Performance On The Regional Financial Management Agency Of Seluma District - Juliansyah Putra; Sri Handayani; Ermy Wijaya (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The ipurpose iof ithis istudy iwas ito idetermine ithe ieffect iof iemotional iintelligence iand iorganizational icommitment itogether ion iemployee iperformance iat ithe iRegional iFinancial iManagement iAgency iof iSeluma iRegency. iThe isample iin ithis istudy iwere i74 iemployees iat ithe iRegional iFinancial iManagement iAgency iof iSeluma iRegency. iCollecting idata iusing ia iquestionnaire iand ithe ianalytical imethod iused iis imultiple ilinear iregression, idetermination itest iand ihypothesis itesting. i iThe iresults iof ithe iregression ianalysis ishowed iY i= i9.714 i+ i0.325X1 i+ i0.454 iX2, ithis idescribes ia ipositive iregression idirection, imeaning ithat ithere iis ia ipositive iinfluence ibetween iX1 i(emotional iintelligence) iand iX2 i(organizational icommitment) ion iperformance i(Y). iIt imeans ithat iif ithe ivariables iof iemotional iintelligence iand iorganizational icommitment iincrease, iit iwill iincrease iperformance. iThe ivalue iof ithe icoefficient iof idetermination iis i0.470. iThis imeans ithat iX1 i(emotional iintelligence) iand iX2 i(organizational icommitment) iaffect iperformance i(Y) iby i47% iwhile ithe iremaining i53% iis iinfluenced iby iother ivariables inot iexamined iin ithis istudy. iEmotional iintelligence ihas ia isignificant ieffect ion iemployee iperformance iat ithe iRegional iFinancial iManagement iAgency iof iSeluma iRegency ibecause ithe itcount iis igreater ithan ittable i(3.419 i> i1.666) iand ithe isignificant ivalue iis i0.001 iless ithan i0.05. iOrganizational icommitment ihas ia isignificant iinfluence ion iemployee iperformance iat ithe iRegional iFinancial iManagement iAgency iof iSeluma iRegency ibecause ithe ivalue iof itcount iis igreater ithan ittable i(4.960 i> i1.666) iand ithe isignificance ivalue iof i0.000 iis iless ithan i0.05. iThe iresults iof ihypothesis itesting isimultaneously i(F itest) ior itogether ihave ia isignificance ivalue iof i0.000 iwhich iis ismaller ithan i0.05 iand iFcount i> iFtable i(31.473 i> i3.13). iThis imeans ithat ithe ivariables iof iemotional iintelligence iand iorganizational icommitment ihave ia isignificant iinfluence itogether ion iemployee iperformance iat ithe iSeluma iRegency iRegional iFinancial iManagement iAgency